Catabolite repression of chloroplast development in Euglena - Monroy, Antonio F. (1984)
Two-dimensional gel electrophoresis resolved total cellular protein from Euglena gracilis Klebs var. bacillaris Cori into 640 polypeptides detectable by silver staining. The addition of 84 mM ethanol to dark-grown resting carbon-starved cells increased the relative amounts of 6 polypeptides and decreased the relative amounts of 3 polypeptides. The addition of 84 mM malate to resting cells increased the relative amounts of 3 of the ethanol-induced polypeptides, suggesting that the induction of these polypeptides represents a generalized response to the provision of a utilizable carbon source, a nutritional shift up, rather than a specific response to ethanol addition. Exposure of dark-grown resting Euglena to light increases the relative amounts of 79 polypeptides encoded by the nuclear as well as the chloroplast genome and decreases the relative amounts of 72 polypeptides. Ethanol but not malate specifically inhibited all of the light-dependent changes in polypeptide levels, indicating that chloroplast development in Euglena is a catabolite-sensitive process.